Frequent Oxygen Desaturation During Sleep on the Day of Bronchoscopy Evaluated by Continuous Pulse Oximeter Monitoring - KAWANAMI, Toshinori; ISHIMOTO, Hiroshi; NOGUCHI, Shingo; KATO, Tatsuji; YATERA, Kazuhiro; MUKAE, Hiroshi; CHOJIN, Yasuo (Journal of UOEH, 2017)
To perform a bronchoscopy safely, it is very important to make a risk assessment before and after the procedure. There have been no reports of hypoxemia during sleep on the day after a bronchoscopic examination; therefore, we evaluated the oxygen saturation status during sleep on the days before and after bronchoscopy. Thirty patients that underwent bronchoscopy were studied. Continuous pulse oximetry monitoring was performed on the day before bronchoscopy and the day when the bronchoscopy was performed. The average oxygen saturation levels and the oxygen desaturation index (ODI) were evaluated. There was a significant increase (P < 0.05) in the ODI-3% during sleep on the day of the bronchoscopy compared to the day before the bronchoscopy. Clinicians should pay careful attention to hypoxia not only during bronchoscopy, but also during sleep on the night following the procedure.